Developing Learning Media Using Online Prezi into Materials about Optical Equipments (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2017)
The instructional media used at schools are not maximized. Therefore, researchers developed an internet-based instructional media using Prezi online software. The objectives of this study are: (1) to describe the instructional medium validity using Prezi; (2) to describe the practicality of Prezi medium as an evaluation from students’ questionnaire responses; and (3) to describe the effectiveness of Prezi medium seen from students’ learning outcomes. This media development refers to the KEMP model development. The instruments used were in the form of media validation sheet, student questionnaire responses, and achievement test. The results showed that: (1) the validity of the medium category is very valid; (2) the practicality of the medium is on the very practical category; (3) the effectiveness of the medium is on the effective category. It is concluded that the Online Prezi instructional medium which was developed is eligible for use in learning.